2014
DOI: 10.1016/j.otsr.2014.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of bipolar radial head prosthesis to treat complex radial head fractures in 22 patients with a mean follow-up of 50 months

Abstract: IV, retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…The mean MEPS was 79, quick-DASH score 21, and 3 patients had residual postero-lateral instability, and four implants had been removed during the observation time (Allavena et al 2014).…”
Section: Development and Use Of Radial Head Prosthesesmentioning
confidence: 99%
See 4 more Smart Citations
“…The mean MEPS was 79, quick-DASH score 21, and 3 patients had residual postero-lateral instability, and four implants had been removed during the observation time (Allavena et al 2014).…”
Section: Development and Use Of Radial Head Prosthesesmentioning
confidence: 99%
“…Using a design with a stem that is meant to be fixed in the proximal radius medullary canal (press-fit) Flinkkila et al reported a loosening rate of 32% and 24% of the implants had to be removed (Flinkkila et al 2012), fig 37. Allavena et al, using a bi-polar implant with a fixed stem, reported 41% with signs of loosening and 18% of implants required removal (Allavena et al 2014).…”
Section: Loss Of Reduction Mal-union Andmentioning
confidence: 99%
See 3 more Smart Citations